Yahoo Answers is shutting down on 4 May 2021 (Eastern Time) and, as of 20 April 2021 (Eastern Time), the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

Geometry doubt....?

Update:

O is a random point on MN . 

CO is extended upto C' .

BO is extended upto B' .

Update 2:

Great solution sir (@atsuo ) ! 

Thank you very very much ! 

_______________________________

Very smart approach sir (@Pope) ! 

Thank you very very much ! 

Update 3:

Amazing solution ! 

Thank you so so much dear sir ! (@Indica) 

Attachment image

4 Answers

Relevance
  • atsuo
    Lv 6
    2 months ago
    Favourite answer

    Let MO = x and ON = y. And let S(@) be the area of @.

    We know BC = 2MN = 2(x+y) = 2x+2y, so

    BC' : MC' = 2x+2y : x

    BM = BC' - MC', so

    BC' : BM = 2x+2y : x+2y

    BC' = BM*(2x+2y)/(x+2y)

    AM = BM, so BM = (1/2)BA. Therefore

    BC' = (1/2)BA*(2x+2y)/(x+2y) = BA*(x+y)/(x+2y)

    So S(C'BC) = S(ABC)*[(x+y)/(x+2y)] ---(#1)

    And C'A = BA - BC' = BA*y/(x+2y) ---(#2)

    Similarly, if we exchange x←→y and B←→C  then we can find

    CB' = CA*(x+y)/(2x+y)

    S(B'BC) = S(ABC)*[(x+y)/(2x+y)] ---(#1')

    B'A = CA - CB' = CA*x/(2x+y) ---(#2')

    Next, we can find

    S(Red) = (1/2)C'A*B'A*sin(∠BAC)

    = (1/2)[BA*y/(x+2y)][CA*x/(2x+y)]*sin(∠BAC) ... by (#2),(#2')

    = (1/2)[BA*CA*sin(∠BAC)]*[xy/((x+2y)(2x+y))]

    = S(ABC)*[xy/((x+2y)(2x+y))] ---(#3)

    And the height of △BOC is 1/2 of the height of ABC, so

    S(OBC) = S(ABC)*[1/2] ---(#4)

    The area of quadrilateral AC'OB' becomes

    S(AC'OB') = S(ABC) - [S(C'BC) + S(B'BC) - S(OBC)]

    = S(ABC)*[1 - ((x+y)/(x+2y) + (x+y)/(2x+y) - 1/2)] ... by (#1),(#1'),(#4)

    = S(ABC)*[1 - (2(x+y)(2x+y) + 2(x+y)(x+2y) - (x+2y)(2x+y))/(2(x+2y)(2x+y))]

    = S(ABC)*[1 - (4x^2+7xy+4y^2)/(2(x+2y)(2x+y))]

    = S(ABC)*[3xy/(2(x+2y)(2x+y))]

    S(Green) = S(AC'OB') - S(Red)

    = S(ABC)*[3xy/(2(x+2y)(2x+y)) - xy/((x+2y)(2x+y))]

    = S(ABC)*[xy/(2(x+2y)(2x+y)]

    Therefore, S(Red)/S(Green)

    = [xy/(x+2y)(2x+y)] / [xy/(2(x+2y)(2x+y))]

    = 2 <--- the answer

  • Indica
    Lv 7
    2 months ago

    This might be of interest  ....

    Attachment image
  • Pope
    Lv 7
    2 months ago

    Here is a trick I used to employ in exams when I found myself running out of time. I would take a limiting case or a special case. For this question, let me take a special case, where point O is the midpoint of MN. Surely you see all the parallel lines and similar triangle resulting from this relation.

    ∆OB'N ~ ∆BB'C

    B'N : B'C = ON : BC = 1 : 4

    B'N : NC = 1 : 3

    B'N : AN = 1 : 3

    AB' : B'N = 2 : 1

    This ratio is equal to the ratio of heights of ∆AB'C' and ∆OB'C', where they have common base B'C'. That therefore is the ratio of areas.

    This would never do as a proof for the general case. However, it does solve this one case. If this ratio is not the same in all cases, then the question itself is incomplete.

    Attachment image
  • Anonymous
    2 months ago

    The question is incomplete as it doesn't explain how points B', C' and O are chosen.

Still have questions? Get answers by asking now.